Local culture-based community development in Subang Regency, West Java - Abu Huraerah; Riany Laila Nurwulan; Peter Voo Su Kiong (EMPATI, 2023)
The purpose of this study are to describe the elements that influence local culture and local culture that supports community development at Banceuy, Sanca Village, Ciater District, Subang Regency, West Java Province. This study uses a qualitative descriptive research method with a case study approach. Primary data collection techniques include interviews, observation, document study and focus group discussions. Meanwhile, secondary data sources were obtained through searching various references such as books and journals. The informant selection technique was carried out through purposive sampling. The validity of the data using triangulation of sources and data analysis techniques through data reduction, data display and conclusion/verification. In detail, data analysis uses the coding manual consists of open coding, axial coding, and selective coding. The main factors influencing local culture at Banceuy, Sanca Village, Ciater District, Subang Regency, West Java Province are geography, natural charm, history, and economy. Meanwhile, the local culture for community development are ritual, art, environmental tourism, mutual cooperation, and cultural tourism. Local culture can be a driving force in community development and should be considered in making development policies in the region. Local culture is a community cultural heritage that can support the community's economy. Local culture can be used as a participatory approach in community development.